2015
DOI: 10.1177/1049732315617217
|View full text |Cite
|
Sign up to set email alerts
|

Health Conditions Prior to Imprisonment and the Impact of Prison on Health

Abstract: Detained women have certain health conditions prior to incarceration and these conditions can improve, worsen, or remain the same in prison, depending on the prisoner's background, the characteristics of the prison, and the arrest experience. This study investigated the health of detained women and the influence of incarceration from their perspective. Three focus groups were conducted among 15 inmates, and data were analyzed according to thematic analysis procedures. Detainer's health backgrounds varied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
(53 reference statements)
2
28
0
2
Order By: Relevance
“…Data from Portugal indicated that incarceration had a positive influence on the health of individuals with drug addiction, but not for individuals with other mental health problems (Alves et al, 2016). There is good evidence for opioid-substitution programs in prisons (Fazel et al, 2016).…”
Section: Interpretation and Comparison With The Literaturementioning
confidence: 99%
“…Data from Portugal indicated that incarceration had a positive influence on the health of individuals with drug addiction, but not for individuals with other mental health problems (Alves et al, 2016). There is good evidence for opioid-substitution programs in prisons (Fazel et al, 2016).…”
Section: Interpretation and Comparison With The Literaturementioning
confidence: 99%
“…Manoma, kad nesėkminga adaptacija pataisos įstaigoje siejasi su mažesne motyvacija keisti savo nusikalstamą elgesį ir recidyvu (Loper, 2002;Zamble & Porporino, 1988). Be to, visos išsivysčiusios šalys vadovaujasi vienoda ideologija, kad laisvės atėmimo bausmė neturėtų būti žalojanti, o pataisos įstaigos ir jų režimas -didinti nuteistųjų kančių, todėl svarbu žinoti, kaip įkalinimas veikia asmenį (Alves, Maia, & Teixeira, 2016;Porporino & Zamble, 1984). Nepaisant to, Lietuvoje tyrimų šia tema vis dar trūksta, o didžioji dauguma užsienio tyrimų buvo atlikti aukšto pragyvenimo lygio šalyse, t. y., Jungtinėse Amerikos Valstijose, Kanadoje, Danijoje ir t. t. (Walker et al, 2014).…”
unclassified
“…;Howerton et al (2007);Plugge, Douglas, and Fitzpatrick (2008);Shen (2016); andSmirnova and Owens (2017) Health database or records 8Chambers (2009);Hassan, Edge, Senior, and Shaw (2013);Khaw, Stobbart, and Murtagh (2007);Newman, Cashin, and Waters (2015); andTopp et al (2016) Program participation 19 Boothby (2011);Bourke et al (2012);Carlin (2005);Drapeau, Korner, Granger, and Brunet (2005); and Mahoney, Chouliara, and Karatzias (2015) Linked research, researcher contacts 11Alves, Maia, and Teixeira (2016); Copes et al (2013); Haley et al (2014); Harawa, Sweat, George, and Sylla (2010); Loeb and Steffensmeier (2011); Plugge et al (2008); Treloar, McCredie, and Lloyd (2015); and Wainwright et al (2017) Resident in certain prison section/unit 6 Bennett (2014); de Viggiani (2007); Gilham (2012); Harner and Riley (2013); Kenning et al (2010); and Ralphs, Williams, Askew, and Norton (2017) Response to flyers and posters 21 Blagden, Winder, and Hames (2014); Cobb and Farrants (2014); Condon et al (2007); Dinkel and Schmidt (2014); Easterling and Feldmeyer (2017); Enders, Paterniti, and Meyers (2005); Harner, Hentz, and Evangelista (2011); Oliver and Hairston (2008); and Pritchard et al (2014) Health-care provider 20 Baker, Wright, and Hansen (2013); Carlson, Sexton, Hammar, and Reese (2011); Feron, Tan, Pestiaux, and Lorant (2008); Guin (2009); Hassan et al (2013); Mangnall and Yurkovich (2010); Soffer and Ajzenstadt (2010); and Yap et al (2014) Prison staff 10 Hefler, Hopkins, and Thomas (2016); Pinheiro, de Araujo, de Vasconcelos, and do Nascimento (2015); Ralphs et al (2017); Todrys and Amon (2011); and Weldon and Gilchrist (2012) Prison manager/administration 3 de Guzman, Imperial, Javier, and Kawasaki (2017); Loeb et al (2013)(2014); DeHart (2008); Earle (2011); Einat (2009); Fogel et al (2014); Rahmah, Blogg, Silitonga, Aman, and Power (2014); Smirnova and Owens (2017); and Topp et al (2016) Attendees at nonaffiliated meeting/event 3 Hefler et al (2016); Schonberg, Bennett, Sufrin, Karasz, and Gold (2015); and Woodall et al , & Zamith-Cruz (2011); Carlson et al (2011); Easterling and Feldmeyer (2017); Haley et al (2014); Hatton et al (2006); Machado and Silva (2012); Mercer et al (2015); Schonberg et al (2015); Soffer and Ajzenstadt (2010); and Weldon and Gilchrist (2012) All participants in a program 9 Akerman and Geraghty (2016); Billington, Longden, and Robinson (2016); Boothby (2011); Drapeau et al (2005); Mahoney et al (2015); Miller, Tillyer, and Miller (2012); O'Grady, Rolvsjord, and McFerran (2015); and Walton and Duff (2017) Purposive for selected characteristic(s) 15 Baker et al (2013); Borrill, Snow, Medlicott, Teers, and Paton (2005); de Guzman et al (2017); Fogel et al (2014); Garrett (2010); Howerton et al (2007); Kennedy (2014); Marzano, Ciclitira, and Adler (2012); Newman et al (2015); Ralphs et al (2017); Schneider and Feltey (2009); and Sondhi et al (2016) Purposive for variation of characteristics or views 20 Alves et al (2016); Andrinopoulos et al (2011); Bowen e...…”
mentioning
confidence: 99%